2022
DOI: 10.3390/sym14101976
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Urdu Digits Dataset with Demonstration of an Efficient and Robust Noisy Decoder-Based Pseudo Example Generator

Abstract: In the present work, we propose a novel method utilizing only a decoder for generation of pseudo-examples, which has shown great success in image classification tasks. The proposed method is particularly constructive when the data are in a limited quantity used for semi-supervised learning (SSL) or few-shot learning (FSL). While most of the previous works have used an autoencoder to improve the classification performance for SSL, using a single autoencoder may generate confusing pseudo-examples that could degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The output gate is composed of the activation functions σ and tanh, whose update equation is ( 6), and finally, the update of h t is completed by Eq. (7).…”
Section: Long Short-term Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The output gate is composed of the activation functions σ and tanh, whose update equation is ( 6), and finally, the update of h t is completed by Eq. (7).…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…Artificial neural network (ANN) is a viable solution to the above problems as it provides low computational cost solutions to complicated issues [5][6][7]. In recent years, related scholars have used ANN to construct the mapping relationship between RFID tag antenna dimensions and EM responses to predict the EM performance of the antenna, which saves time in calculating antenna performance and improves antenna design efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, driven by the advancement of bigdata-based architectures (Khan et al, 2022a), deep learning (DL) techniques (LeCun et al, 2015) have shown great promises in computer vision (Voulodimos et al, 2018;Roy and Bhaduri, 2021;Roy et al, 2022c;Roy and Bhaduri, 2022;Roy et al, 2022a), object detection (Zhao et al, 2019;Chandio et al, 2022;Roy et al, 2022b;Singh et al, 2023a), image classification (Rawat and Wang, 2017;Irfan et al, 2021;Jamil et al, 2022;Khan et al, 2022b), damage detection (Guo et al, 2022;Glowacz, 2022Glowacz, , 2021 brain-computer interfaces (Roy, 2022b,a,c;Singh et al, 2023b) and across various scientific applications (Butler et al, 2018;Ching et al, 2018;Bose and Roy, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Because this makes it possible for individual fish to be more easily identified, it is of greater relevance in terms of directing the expansion of the fish farming industry. At this time, the bulk of solutions for fish individual recognition (FIR) [ 27 ] make use of DL models that are built on the framework for fish recognition. The framework for fish recognition consists of three processes: fish object detection, fish feature extraction, and fish feature comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the SSD method is fast, a large number of the parameters have to be supplied manually, and the process of debugging is challenging. The YOLO series approach is well suited for identifying individual fish because of its rapid speed [ 27 ], high accuracy [ 28 ], simple debugging, and real-time detection capabilities [ 29 ].…”
Section: Introductionmentioning
confidence: 99%